"We do it ourselves": strengths and opportunities for improving the practice of harm reduction - Kasey Claborn; Jake Samora; Katie McCormick; Quanisha Whittfield; Frederic Courtois; Kyle Lozada; Daniel Sledge; Annie Burwell; Sandra Chavez; Jamie Bailey; Chris Bailey; Chelsea Dalton Pederson; et al. (BMC, 2023)
Abstract Background Unprecedented increases in substance-related overdose fatalities have been observed in Texas and the U.S. since the onset of the COVID-19 pandemic and have made clear there is considerable need to reduce harms associated with drug use. At the federal level, initiatives have called for widespread dissemination and implementation of evidence-based harm reduction practices to reduce overdose deaths. Implementation of harm reduction strategies is challenging in Texas. There is a paucity of literature on understanding current harm reduction practices in Texas. As such, this qualitative study aims to understand harm reduction practices among people who use drugs (PWUD), harm reductionists, and emergency responders across four counties in Texas. This work would inform future efforts to scale and spread harm reduction in Texas. Methods Semi-structured qualitative interviews were conducted with N = 69 key stakeholders (25 harm reductionists; 24 PWUD; 20 emergency responders). Interviews were transcribed verbatim, coded for emergent themes, and analyzed using Applied Thematic Analysis with Nvivo 12. A community advisory board defined the research questions, reviewed the emergent themes, and assisted with interpretation of the data. Results Emergent themes highlighted barriers to harm reduction at micro and macro levels, from the individual experience of PWUD and harm reductionists to systemic issues in healthcare and the emergency medical response system. Specifically, (1) Texas has existing strengths in overdose prevention and response efforts on which to build, (2) PWUD are fearful of interacting with healthcare and 911 systems, (3) harm reductionists are in increasing need of support for reaching all PWUD communities, and (4) state-level policies may hinder widespread implementation and adoption of evidence-based harm reduction practices. Conclusions Perspectives from harm reduction stakeholders highlighted existing strengths, avenues for improvement, and specific barriers that currently exist to harm reduction practices in Texas.